Forensic Face Matching 2021
DOI: 10.1093/oso/9780198837749.003.0004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Professional Expertise in Unfamiliar Face Matching

Abstract: Deciding whether or not two images are of the same unfamiliar face is an important task in many professions. These decisions are a critical part of modern identity verification processes with direct—and often profound—consequences for individual rights and the security of society. As a result, the public expect the people entrusted with these decisions to perform accurately. But do they? Here we review 29 published tests comparing face matching accuracy in professional and novice groups. Twelve of these tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…Interestingly, facial examiners’ trajectory of perceptual learning in face identification—from intuitive, holistic processing to more analytic, featural comparison (see White et al, 2015)—is precisely the opposite shift that is typically thought to characterize perceptual learning and the development of expertise more generally (see Chase & Simon, 1973; Kahneman & Klein, 2009; White et al, 2021). The effectiveness of feature-based comparison observed here therefore has broader implications for the study of perceptual expertise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, facial examiners’ trajectory of perceptual learning in face identification—from intuitive, holistic processing to more analytic, featural comparison (see White et al, 2015)—is precisely the opposite shift that is typically thought to characterize perceptual learning and the development of expertise more generally (see Chase & Simon, 1973; Kahneman & Klein, 2009; White et al, 2021). The effectiveness of feature-based comparison observed here therefore has broader implications for the study of perceptual expertise.…”
Section: Discussionmentioning
confidence: 99%
“…In Towler et al (2017) we collected feature similarity ratings from a group of experts—specialist professionals known as facial examiners —who consistently outperform novices on unfamiliar face matching tasks (see White et al, 2021). Facial examiners’ identification accuracy was 14% higher than novices’ (89% vs. 78%), and their ratings of facial feature similarity were much more diagnostic of identity (Cohen’s d = 1.44).…”
mentioning
confidence: 99%
“…Professional examiners typically outperform novices on tasks within their domain of experience: facial examiners outperform novices on facial comparison (Phillips et al, 2018;White, Phillips, et al, 2015;White et al, 2020); fingerprint examiners outperform novices on fingerprint comparison (Busey & Vanderkolk, 2005;Tangen et al, 2011;Ulery et al, 2011); firearm examiners have a higher rate of correct matches than do standard computer algorithms in firearm comparison (Mattijssen et al, 2021); and document examiners are better at avoiding Bethany Growns and James D. Dunn contributed equally to this work.…”
mentioning
confidence: 99%
“…Because of this ability, law enforcement and security organizations employ superrecognizers (1,14,32,36,37). Consistently, findings show that facial examiners are highly accurate at facial comparisons (30,46,49,50,52); similarly, other studies found that super-recognizers are also highly accurate (1-3, 6-9, 14-16, 32, 33, 36-38, 40, 44). The first paper directly comparing these two groups reported that they are equally accurate to each other (34).…”
Section: Introductionmentioning
confidence: 52%